Peggunaan Metode Observasi Variasi LKS Word Square untuk Meningatkan Hasil Belajar Materi Foto Sintesis pada Siswa SMP - Sugito Sugito (Academy of Education Journal, 2018)
Learning Biology is part of science that emphasizes providing hands-on experience. During this time students have difficulty learning Photosynthesis material because there are many things that must be proven by experiments and learning that are abstract with the lecture method. To help students understand the material, learning is applied with the observation method which is varied with LKS Word square. This research was designed through Classroom Action Research (CAR). The purpose of this study was to determine the increase in learning outcomes of reproductive material in plants and animals through the application of the observation method which was varied with the LKS Word square in class VII A semester 1 of SMP Negeri 1 Binangun in the academic year 2015/2016. The subject of this research is class VII A SMP Negeri 1 Binangun with a total of 32 students. This research was conducted in two cycles. Each cycle consists of 4 stages, namely: planning (planning), implementation (acting), observation (observing), and reflection (reflecting). Indicators of the success of this study were (1) an increase in the percentage of students who received a score of = 61 or the number of students who studied thoroughly increased to 85%, (2) completeness of classical activity =75%. Based on the results of the study obtained data increase in the percentage of achievement of classical learning completeness in the first cycle 83.33% and the second cycle 91.67%, while the classical activity in the first cycle 61.11% and the second cycle 80.56%. The conclusion of this study is that through the application of the observation method that is varied with the Word Square worksheet on Photosynthesis material can improve student learning outcomes in class VII A semester 1 of SMP Negeri 1 Binangun in the academic year 2015/2016. While the suggestion of this research is that the method of observation varied with Word Square Worksheet needs to be applied to other science teaching materials because the observation method varied with Word Square worksheet makes it easier for students to understand the material being studied.